An unusual gastric biopsy - Dmitry Zinovkin,; Mikhail Zhandarov,; Elizaveta Bredyhina,; Md Zahidul Islam Pranjol, (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Zinovkin D, Zhandarov M, Bredyhina E, Parajnol MZI. An unusual gastric biopsy. Turk J Gastroenterol 2020; 31(1): 76-7.